Interregional Consumption Patterns and Their Contribution to Economic Growth - Nur, Rasyidusman Hannamara Furqan (Riwayat: Educational Journal of History and Humanities, 2025)
Household consumption is one of the main drivers of economic growth, but the differences in consumption patterns between regions have not been studied in depth. This study aims to analyze the contribution of interprovincial consumption patterns to economic growth by sampling five representative provinces, namely Aceh, Jakarta, West Java, Bali, and West Papua, which were selected based on the diversity of economic structure and consumption characteristics. The study used a quantitative approach with annual data for the period 20152024 and was analyzed through panel regression to see the relationship between household consumption and economic growth. The results showed that household consumption had a positive and significant effect on economic growth across the sample provinces, with variations in the level of influence reflecting the economic conditions of each region. Provinces with urban consumption bases such as Jakarta and West Java contribute more than areas with low consumption capacity such as West Papua. This study concludes that consumption patterns between regions not only reflect differences in people's purchasing power, but also become an important factor in the direction of national economic development, so that it can be the basis for more inclusive and equitable policy formulation.